ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK DAN KUALITAS PELAYANAN RESTORAN CEPAT SAJI McDONALD’S - Eka Purna Yudha; Afif Ahmad Rifai; Aqila Shafa Adela (Universitas Galuh, 2022)
The quality of a product and service to consumers is a major concern in the trade and service industry. One of the efforts that can be done in increasing the competitiveness of the company is to increase customer satisfaction. The purpose of this study is to 1) determine consumer interest in the products and services provided by McDonald's, 2) analyze the performance of McDonald's in providing satisfaction to its customers, 3) analyze the level of customer satisfaction regarding the products and services provided. The data collection carried out in this study was carried out by distributing 50 questionnaires to McDonald's consumers. Importance Performance Analysis method is used to analyze the effect of product quality and service quality on customer satisfaction. The Customer Satisfaction Index method is used to measure the overall level of customer satisfaction. The results of this study indicate that consumers.